DIMENSI PSIKOLOGIS DALAM PEMBENTUKAN KARAKTER KEBANGSAAN - Lusiawati, Ira (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2025)
The complexity of global developments also affects the life of the nation. The power spread by the two main axes of the world can change the orientation that becomes the commitment and ideals of the nation. From the beginning, it was determined to form a character that is a characteristic of national nature but changed course and headed towards one of the axes that were competing for influence. This condition was experienced by Indonesia when the world constellation changed and created a transitional situation before a new power emerged. Indonesia's direction towards a particular axis had disturbed the psychological mentality of the nation's children because the life of the nation and state had deviated from the ideals. However, because of the strong awareness and spirit of nationalism, the direction that had changed finally returned to the true characteristics and nature of the nation. Based on these conditions, this study aims to determine the psychological dimension in forming national character. The method used is descriptive qualitative with literature methods. The results of the study show that the formation of national character must take into account the psychological dimension in order to raise awareness of identity and pride in one's own nation. Another interest is that generations who are aware of their national spirit will be a reminder when the nation's leaders take steps by directing themselves to one of the world powers that is different from the national vision.